Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Transnational Communication and Critical/Cultural Studies, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

“To Whom Do Our Bodies Belong?”: Being Queer in Chinese DV Documentary - Robinson, Luke (DV-made China : digital subjects and social transformations after independent film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.
Keywords: 1-Cinéma; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé